Relationship between Sea Surface Temperature and Chlorophyll-a Concentration with Tuna Catch in Ternate Island Waters - Bafagih, Aisyah; Laitupa, Ibnu W. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This study was conducted during January - March 2023 in the waters of Ternate Island with the aim of examining sea surface temperature and chlorophyll-a parameters and their relationship with the catch of tuna (Euthynnus affinis) to get the optimum value of the two oceanographic factors for the presence of tuna. The use of field survey method for data collection and assessment with statistical analysis and GIS analysis. The results showed that the value of oceanographic factors, namely sea surface temperature during the study ranged from 26.8-31.7 oC and had a real influence on the catch of tuna with a correlation coefficient of 0.74, where there was a tendency if the sea surface temperature was higher than the average temperature (30.14 oC) then the catch would decrease. For the chlorophyll-a parameter, the value ranges from 0.120-0.440 mg/m3 and also has a significant effect on the catch of mackerel with a detemination coefficient of 0.74. and there is a tendency that an increase in the value of chlorophyll-a concentration is directly proportional to the increase in the number of mackerel catches. The optimum values of sea surface temperature and chlorophyll-a concentration for mackerel distribution in Ternate Island waters are 27 - 30.9 oC for sea surface temperature and chlorophyll-a concentration values above 0.1 mg/m3, respectively.